The Monetary Policy in the Development of Public-Private Partnership (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, researched country's monetary and credit policy, the role of small business in the economy based on public-private partnership, its essence, importance and necessity, it’s impact on export-import relations, inflation targeting and the measures taken by the Central Bank. In this regard, simultaneous thoughts and opinions on the development of public-private partnership regarding the effective use of monetary instruments, export and import opportunities, human capital and scientific potential in the stabilization of the country's economy in a changing and global world, the transition from a single-system development system to a multi-system system, strengthening and upgrading given.